2002
DOI: 10.1177/0042085902372003
|View full text |Cite
|
Sign up to set email alerts
|

Campus Culture and the Experiences of Chicano Students in a Predominantly White University

Abstract: The primary goal of this study was to uncover the elements of campus culture that hindered or supported Chicano student persistence in college. The first set of findings describes the elements of campus culture that hindered the persistence of Chicano students. These elements were identified as three cultural systems of asymmetrical representations, labeled (a) the social world, (b) the physical world, and (c) the epistemological world. It was found that within each of these three worlds, dominant White cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
113
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 20 publications
5
113
0
1
Order By: Relevance
“…Students interpret messages of the low institutional value placed on African American student retention as campus resources dedicated to this effort are physically marginalized from the campus center. This is similar to the findings related to the "physical world" in González's (2002) study that considered the lack of representation of Chicano culture among campus spaces and buildings and its impact on Chicano students.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Students interpret messages of the low institutional value placed on African American student retention as campus resources dedicated to this effort are physically marginalized from the campus center. This is similar to the findings related to the "physical world" in González's (2002) study that considered the lack of representation of Chicano culture among campus spaces and buildings and its impact on Chicano students.…”
supporting
confidence: 87%
“…Their experiences present the culture shock they experience as African American women at their institution. This resembles the experiences of Chicano students in González's (2002) study of campus culture. Within the "social world" of the campus culture, participants in González's study also reported feelings of alienation and marginalization, heightened by the lack of representation of Chicanos among the faculty and students.…”
supporting
confidence: 60%
“…While Tinto's theory recognizes the impact of family to pre-college commitment, to truly be descriptive of students who espouse collectivist cultural orientations, the theory must also recognize the potential for families and friends from home, or what I refer to broadly as home social systems, to support students once they arrive at college. This assertion is based on several conceptual critiques of Tinto's theory (see Kuh & Love, 2000;Hurtado, 1997;Rendon, Jaloma, & Nora, 2000;Nora, 2001;Tierney, 1992Tierney, , 1999 and findings from numerous studies that have concluded that minority students can gain tremendous support from families, friends, and other members of their home communities (Cabrera, Nora, Terenzini, Pascarella, & Hagedorn, 1999;Delgado Bernal, 2002;Eimers & Pike, 1996;Gloria, Robinson Kurpius, Hamilton, & Wilson, 1999;Gonzalez, 2000;Guiffrida, 2004Guiffrida, , 2005Hendricks, Smith, Caplow, & Donaldson, 1996;Hurtado, Carter, & Spuler, 1996;Nora & Cabrera, 1996;Rosas & Hambrick, 2002).…”
Section: ) Theorymentioning
confidence: 99%
“…10. Gonza´lez (2002) specifically identifies the alienating and marginalizing contexts of the predominantly White university as social, physical, and epistemological spaces. 11.…”
Section: The Urban Reviewmentioning
confidence: 99%